Case of tumour rickets. - Moncrieff, M W (1978)
A 10-year-old boy, with widespread soft tissue tumours of bone, developed hypophosphataemic rickets due to impaired renal tubular reabsorption of phosphate. Biopsy of the largest tumour showed a nonosteogenic fibroma. We believe this boy is another example of 'tumour rickets', as other causes of rickets were excluded clinically and biochemically. Cases of rickets or osteomalacia associated with a tumour, have generally been reported to be cured by surgical removal of the tumour, implicating it as the cause of rickets or osteomalacia. Owing to the large number of tumours in this boy, surgical removal was not possible, and he required large doses of vitamin D, together with oral phosphate, before his rickets healed. It is suggested that the tumour produces a phosphaturic hormone.